1999
DOI: 10.4269/ajtmh.1999.60.848
|View full text |Cite
|
Sign up to set email alerts
|

Long-term persistence of cellular hyporesponsiveness to filarial antigens after clearance of microfilaremia.

Abstract: Abstract. The persistence of parasite-specific cellular hyporesponsiveness after clearance of blood microfilariae (mf) was studied in 18 individuals who had been treated with a single dose of ivermectin, diethylcarbamazine, or a combination 2-3 years previously and who had initially cleared their parasitemia. At recruitment into the present study, 50% were again mfϩ and 50% remained mfϪ. There were no significant differences between the mfϩ and mfϪ groups in the amount of interferon-␥ (IFN-␥) produced by perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…However, the cause-effect relationship between these in vitro parameters and clinical and infection status of the hosts are still not clear. Reversal of responses observed after chemotherapy was also found to be only transient and the hyporesponsiveness reestablished after a period of time [9]. These limited but valuable studies have shown that qualitatively the immune response phenotypes are sustained in both the cohorts over 13-18 years.…”
Section: Antimicrofilarial Immunitymentioning
confidence: 89%
“…However, the cause-effect relationship between these in vitro parameters and clinical and infection status of the hosts are still not clear. Reversal of responses observed after chemotherapy was also found to be only transient and the hyporesponsiveness reestablished after a period of time [9]. These limited but valuable studies have shown that qualitatively the immune response phenotypes are sustained in both the cohorts over 13-18 years.…”
Section: Antimicrofilarial Immunitymentioning
confidence: 89%
“…Our findings thus suggest that stimulation of both Th1‐ and Th2‐helper immune response provide better degree of protection than either a Th1‐ or Th2‐biased stimulation. Immunosuppression has been earlier reported to be accompanied with invasion of infective filarial larvae facilitating their establishment in the vertebrate host (30–34). The immunostimulation provided by withaferin A and different chemotypes during infection mounted sufficient resistance or at least neutralized to some extent the immunosuppression brought about by the invading larvae interfering with its establishment, further growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, and corresponding with our results, Sartono et al (1995) reported an enhanced IFN-γ response of PBMC to specific antigen in Wuchereria bancrofti patients 1 year after DEC application and Henry et al (2001) found increased IL-5 and IFN-γ responses associated with reduced IL-10 synthesis in reaction to specific antigens in ivermectintreated Onchocerca volvulus patients (although >10 years after drug application). In addition, enhanced Th 1 responses were found in onchocerciasis patients, beginning 6 months after ivermectin treatment in spite of persisting microfilariae in the skin in most cases (Gopinath et al 1999). Others could not find any difference in the IFN-γ response to specific antigens between lymphatic filariasis patients found microfilaremic or amicrofilaremic 2-3 years after ivermectin-DEC treatment.…”
Section: Discussionmentioning
confidence: 99%